KOMPARASI RELEVANSI NILAI INFORMASI AKUNTANSI DAN MANAJEMEN LABA SEBELUM DAN SESUDAH ADOPSI IFRS - Sukma, Made Anggia Pramita; Yadnyana, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This research reveals comparability of value relevance and earnings management in the period Post-IFRS and Pre-IFRS. Value relevance of accounting information that used in this research is measured by earnings and book value using Ohlson method. Earnings management is measured by discretionary accruals using Modified Jones Model. Population in this research is all non-financial companies listed on the Indonesia Stock Exchange. This research takes four years of observation. The method of sample selection is purposive sampling. Chow test proves that listed companies engage in increase significantly of value relevance after full IFRS adoption. The results show a significant declining of earnings management after full IFRS adoption proved by paired sample t-test. It is suggested that further research add other variables such as conservatism and timely loss recognition.
Keywords: IFRS, Value Relevance, Earnings Management